Endogenous Firm Entry in an Estimated Model of the U.S. Business Cycle - Sven Offick; Roland Winkler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper explores and quantifies the role of endogenous firm entry in amplifying and propagating shocks to the economy. To this end, we estimate two DSGE models on US data with Bayesian methods: one model with endogenous firm entry and translog preferences and one model without. Both models perform equally well in fitting the data but in doing so the endogenous entry model does not rely on a fairly flexible supply of labor. The presence of firm entry amplifies the effects of productivity and wage mark-up shocks, but it dampens those of aggregate demand and investment-specific technology shocks.
Keywords: E20; E32; C11; 330